2002
DOI: 10.1111/j.1460-2466.2002.tb02567.x
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Interactivity Principle: Effects of Mediation, Propinquity, and Verbal and Nonverbal Modalities in Interpersonal Interaction

Abstract: Early channel reliance research compared different modes of communication to assess relationships among nonverbal and verbal cues. Emerging communication technologies represent a new venue for gaining insights into the same relation-ships. In this article, the authors advance a principle of interactivity as a framework for decomposing some of those relationships and report an experiment in which physical proximity-whether actors are in the same place ("co-located") or interacting at a distance ("distributed")-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
159
2
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(169 citation statements)
references
References 43 publications
6
159
2
2
Order By: Relevance
“…Communication research shows that effective communication needs to incorporate "warm" channels of communication, such as face-to-face discussion (23). Nonverbal cues are crucial to social interaction (24), and evidence suggests that effective healthcare communication involves both verbal and written elements (25). Our sample of attendings confirmed this notion, saying that the ideal handoff took place in person and had some written element.…”
Section: Box 2 Narrative Comments About Handoff Practicessupporting
confidence: 72%
“…Communication research shows that effective communication needs to incorporate "warm" channels of communication, such as face-to-face discussion (23). Nonverbal cues are crucial to social interaction (24), and evidence suggests that effective healthcare communication involves both verbal and written elements (25). Our sample of attendings confirmed this notion, saying that the ideal handoff took place in person and had some written element.…”
Section: Box 2 Narrative Comments About Handoff Practicessupporting
confidence: 72%
“…Research in human communication has shown that brief observations of the bodily, facial, speech, and vocal cues that people display predict these outcomes (Ambady and Rosenthal 1992). Seemingly subtle differences in such cues of interaction partners shape outcomes such as perceptions of their attitudes (Mehrabian 1967), the persuasiveness of their messages (Segrin 1993), and their performance in collaborative work (Burgoon et al 2002).…”
Section: Articlesmentioning
confidence: 99%
“…Many of these studies show degradation of both problem-solving performance and interpersonal communication due to the reduced modes of interaction associated with technology-mediated communication (Doerry, 1996;Olson & Olson, 2000). However, other studies show that people can compensate for and even benefit from restricted interaction (Burgoon et al, 2002;Herring, 1999), and that factors extrinsic to the technology itself may play a role (Walther, 1994). It was not our intent to replicate these results: our focus was on how the roles of external representations in supporting collaboration might change when going online, especially in ways that might affect the relevance of representational guidance.…”
Section: Appropriation Of Representations For Online Collaborationmentioning
confidence: 77%